Barriers to the management of obstructed defaecation according to colorectal surgeons. (July 2017) - Al‐Mozany, N.; Wright, C.; O'Grady, G.; Young, C. J.; Solomon, M. J.
Abstract: Aim: Obstructed defaecation (OD) has a high prevalence and high disease impact; however, patients often experience suboptimal management. This problem reflects the complex pathophysiology of OD as well as health service delivery factors. This study aimed to identify the factors that act as a barrier to effective management of OD as perceived by specialist colorectal surgeons treating this disorder. Method: A postal questionnaire was administered to a bi‐national sampling of colorectal specialists in Australia and New Zealand who were registered with their specialty society. Questions addressed variables relevant in OD management, including clinical access, decision‐making, patient factors and surgeon experience and perceptions, and used Likert scales. Statistical analyses compared surgeon practice variables. Results: The response rate was 68.5% ( n  = 113). Most surgeons managed OD (94%), and preferred to treat OD patients themselves (87%); however, 33% of these respondents were dissatisfied with their management, 46% felt they lacked management expertise and 33% stated they had inadequate expertise in OD investigations. Clinical investigation services were more limited in private than public practice, and many surgeons lacked access to biofeedback (31%). Other barriers included heterogeneity in decision‐making by surgeon age and practice location ( P  < 0.05), dual pathologies (e.g. irritable bowel syndrome) and psychological factors, and limited uptake of multidisciplinary services and standardized (Rome) diagnostic criteria. Conclusion: Barriers to OD management include surgeon‐specific factors, patient‐specific factors and healthcare access factors. Increased utilization of pelvic floor and multidisciplinary services, increased training and standardization of OD investigations and improved access to specialist investigations and allied‐health management services could improve outcomes for OD.